Inequality and the US import demand function - Margarita Katsimi; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2006)
In this paper we build a model of trade in vertically differentiated products and find that income inequality can affect the demand for imports even in the presence of homothetic preferences. The empirical importance of changes in inequality on the demand for imports is then assessed by examining US data for the 1948-1996 period. Using the Johansen (1988) procedure we find that there is no evidence of a long run relationship of a standard imports equation (one including imports, income, and relative prices). However, once we include a measure of inequality in our VAR specification we find not only evidence for the existence of a cointegrating equation in imports, income, relative prices and inequality, but that the evolution of inequality has a large and positive influence on the demand for imports in the US. Moreover we find that our results are robust to alternative methods of estimating cointegration equations.
Keywords: F13; H23; O24; 330